Cardiovascular magnetic resonance characteristics and clinical outcomes of patients with ST-elevation myocardial infarction and no standard modifiable risk factors–A DANAMI-3 substudy - Mazhar, Jawad; Ekström, Kathrine; Kozor, Rebecca; Grieve, Stuart M.; Nepper-Christensen, Lars; Ahtarovski, Kiril A.; Kelbæk, Henning; Høfsten, Dan E.; Køber, Lars; Vejlstrup, Niels; Vernon, Stephen T.; Engstrøm, Thomas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: A higher 30 day mortality has been observed in patients with first-presentation ST elevation myocardial infarction (STEMI) who have no standard modifiable cardiovascular risk factors (SMuRFs) i.e. diabetes, hypertension, hyperlipidemia and current smoker. In this study we evaluate the clinical outcomes and CMR imaging characteristics of patients with and without SMuRFs who presented with first-presentation STEMI. Methods: Patients from the Third DANish Study of Acute Treatment of Patients With ST-Segment Elevation Myocardial Infarction (DANAMI-3) with first-presentation STEMI were classified into those with at least 1, or without any SMuRFs. Results: Of the 2046 patients; 283 (14%) were SMuRFless and 1763 (86%) had >0 SMuRF. SMuRFless patients were older (66 vs. 61 years, p<0.001) with more males (84% vs. 74%, p<0.001), more likely to have left anterior descending artery (LAD) as the culprit artery (50% vs. 42%, p=0.009), and poor pre-PCI (Percutaneous Coronary Intervention) TIMI flow ≤1 (78% vs. 64%; p<0.001). There was no difference in all-cause mortality, non-fatal reinfarction or hospitalization for heart failure at 30 days or at long-term follow-up. CMR imaging was performed in 726 patients. SMuRFless patients had larger acute infarct size (17% vs. 13%, p=0.04) and smaller myocardial salvage index (42% vs. 50%, p=0.02). These differences were attenuated when the higher LAD predominance and/or TIMI 0-1 flow were included in the model. Conclusion: Despite no difference in 30-days mortality, SMuRFless patients had a larger infarct size and smaller myocardial salvage index following first-presentation STEMI. This association was mediated by a larger proportion of LAD culprit and poor TIMI flow pre-PCI.